2021
DOI: 10.1017/s1431927621013751
|View full text |Cite
|
Sign up to set email alerts
|

Na+ and K+ Ions Differently Affect Nucleosome Structure, Stability, and Interactions with Proteins

Abstract: Inorganic ions are essential factors stabilizing nucleosome structure; however, many aspects of their effects on DNA transactions in chromatin remain unknown. Here, differential effects of K+ and Na+ on the nucleosome structure, stability, and interactions with protein complex FACT (FAcilitates Chromatin Transcription), poly(ADP-ribose) polymerase 1, and RNA polymerase II were studied using primarily single-particle Förster resonance energy transfer microscopy. The maximal stabilizing effect of K+ on a nucleos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Andreeva et al further compared the effects of Na + and K + ions on nucleosome structure, stability, and interactions with proteins. The stabilizing effect of K + was noticeably higher than that of Na + and was accompanied by a maximal stabilizing effect on nucleosomes at a concentration of 80–150 mM, while Na + supported a more efficient reorganization of the nucleosome structure by poly(ADP-ribose) polymerase 1 and ATP-independent uncoiling by FACT when compared to K + [ 131 ]. Another modeling study also demonstrated that ions could accumulate at the site between the nucleosomal DNA gyres, which would prevent nucleosome breathing [ 132 ].…”
Section: Multiple Regulatory Factors and Associated Mechanismmentioning
confidence: 99%
“…Andreeva et al further compared the effects of Na + and K + ions on nucleosome structure, stability, and interactions with proteins. The stabilizing effect of K + was noticeably higher than that of Na + and was accompanied by a maximal stabilizing effect on nucleosomes at a concentration of 80–150 mM, while Na + supported a more efficient reorganization of the nucleosome structure by poly(ADP-ribose) polymerase 1 and ATP-independent uncoiling by FACT when compared to K + [ 131 ]. Another modeling study also demonstrated that ions could accumulate at the site between the nucleosomal DNA gyres, which would prevent nucleosome breathing [ 132 ].…”
Section: Multiple Regulatory Factors and Associated Mechanismmentioning
confidence: 99%